Well-being sebagai Mediator Pengaruh Dukungan Sosial terhadap Kecemasan Karir Mahasiswa Tahun Akhir - Jecyka Tri Putri Andiska; Farida Agus Setiawati (Kuras Institute, 2026)
Career anxiety is a common problem experienced by final year students due to academic pressure, social expectations, and uncertainty about future work. This study aims to analyze the effect of social support on students' career anxiety, both directly and indirectly through the mediating role of well-being. The method used is quantitative, with a correlational design, involving final-year students of Yogyakarta State University, selected using a multistage random sampling technique, yielding 452 samples. Data were collected through standardized questionnaires, namely the Career Anxiety Scale (CAS) with a Cronbach's Alpha value of 0.920, the Multidimensional Scale of Perceived Social Support (MSPSS) with a Cronbach's Alpha value of 0.982, and the College Student Subjective Well-being Questionnaire - Revised (CSSWQ-R) with a Cronbach's Alpha value of 0.810. The results of the regression analysis showed that social support had a significant negative effect on career anxiety and a positive effect on well-being. Furthermore, well-being was shown to have a significant negative effect on career anxiety and acted as a partial mediator in the relationship between social support and career anxiety, which initially decreased from 51.7% to 64.3% after the well-being variable was included. In conclusion, social support not only directly reduced career anxiety but also strengthened students' well-being, which in turn helped them face the challenges of the working world with more calm and confidence.